Contribution of (non-)starch polysaccharides to distinctive sensory perception in beer – Significance of their physical and friction characteristics - Rolando Cesar Moreno Ravelo; Christoph Neugrodda; Martina Gastl; Thomas Becker (Current Research in Food Science)
The palate fullness (body) and mouthfeel are important sensory attributes influencing the consumers’ beer preference. Among the several parameters affecting these attributes, recent research suggests that the physical characteristics (molar mass and conformation) of starch (dextrins) and non-starch polysaccharides (arabinoxylans and β-glucans) play a critical role. However, the lack of information regarding the physical state of these polysaccharides in beer hinders the sensory evaluation of each component. A method was recently introduced to isolate and solely characterize the molar mass and conformation of beer's starch and non-starch polysaccharides in solution by AF4-MALS-DRI. Therefore, this research evaluated the relationship between the molar mass and conformation of arabinoxylans, β-glucans, and dextrins with the palate fullness and mouthfeel sensorial perception. Additionally, friction, assessed by soft tribology, was analyzed as a triggering mechanism during oral processing. Grains from different sources modified at a low level (steeping degree as parameter) were used to produce bottom-fermented beers with diverse physical characteristics. Regarding the friction response, the variation of correlation behavior at different sliding velocities suggests that the human sensory panel might perceive the palate fullness and mouthfeel at different stages during oral processing. The multivariate analysis suggests that the conformation ratio, rrms/rhyd, from each polysaccharide triggers a distinctive sensory response, being dextrins related to palate fullness while arabinoxylans and β-glucans to mouthfeel. Furthermore, the beer sample substituted with barley modified at a low level presented an increase of branched dextrins in comparison to the (unsubstituted) control, which was related to its increase in palate fullness intensity.